The consumer on the home front : Second World War civilian consumption in comparative perspective - Berghoff, Hartmut 1960- HerausgeberIn; Logemann, Jan HerausgeberIn; Römer, Felix 1978- HerausgeberIn (Studies of the German Historical Institute London, 2017)
Consumption on the home front during the Second World War : a transnational perspectiv / Hartmut Berghoff -- The home front and food insecurity in wartime Japan : a transnational perspective / Sheldon Garon -- The hidden world of Soviet wartime food provisioning : hunger, inequality, and corruption / Wendy Z. Goldman -- Food consumption in Britain during the Second World War / Ina Zweiniger-Bargielowska -- Deprivation and indulgence : Nazi consumption policy on tobacco / Nicole Petrick-Felber -- 'Not the least of all that you will prize among the blessings of peace' : commercial advertising and imagining the postwar world in Britain / David Clampin -- For the sake of the nation : mobilizing for war in Japanese commercial advertisements 1937-1945 / Annika A. Culver -- Advertising and consumers in Second World War Germany / Pamela E. Swett -- Vicarious consumption : fashion in German media and film during the war years 1939-1943 / Mila Ganeva -- Soviet wartime fashion as a phenomenon of culture and consumption / Sergey Zhuravlev -- Strategic austerity : the Canadian middle path / Bettina Liverant -- From wartime research to postwar affluence : European émigrés and the engineering of American wartime consumption / Jan Logemann -- A consumer society shaped by war : the German experience 1935-1955 / Uwe Spiekermann -- War after war : the Soviet mobilization model and mass consumption in the 1940s and 1950s / Oleg V. Khlevniuk -- The lessons of war : reordering the public and private capacities and dynamics of consumption / Frank Trentmann